A Case Study On Customizing The Microsoft Time Series Algorithm: Tourist Arrival Prediction - Nawzer, H.; Weerasekara, M (NSBM Green University, 2018)
As far as tourism is concerned in Sri Lanka, it is considered as one of a lucrative industry for the country. On the other hand, in the modern computing era business intelligence plays a revolutionary role in uplifting the profits of business organizations. The research is about how the Microsoft Time Series algorithm can be improvised to predict the arrival of tourists. The algorithm employed for the tourists who arrived for Sri Lanka in past few decades. Furthermore, this study discusses the drawbacks of the existing Microsoft Time series algorithm concerning the consideration of the external factors which affects the prediction. Also, this study discusses some of the possible solutions to overcome that issue.
Keywords: business intelligence; tourism; tourist arrival prediction; Microsoft time series algorithm